Forensic analysis of water‐based lubricants using liquid extraction surface analysis high‐resolution tandem mass spectrometry. (12th August 2018) - Hood, Shiona; Peter, Tony; Blanksby, Stephen J.; Marshall, David L.
Abstract : Rationale: Analysis of water‐based personal lubricants can provide pivotal information to law enforcement regarding sexual assault allegations, particularly in the absence of biological evidence. Traditional methodology for the extraction and analysis of water‐based lubricants is cumbersome, time‐consuming, and often not sufficiently selective or sensitive to fully characterise the wide range of chemical components present within complex formulations. Methods: Liquid extraction surface analysis (LESA) was deployed in combination with high‐resolution mass spectrometry (HRMS) and tandem mass spectrometry (MS/MS) to screen a range of water‐based lubricants directly from contaminated cotton fabric. Rehydration of the fabric was the only sample preparation required. Results: Analysis of ten different water‐based lubricants by nano‐electrospray ionisation mass spectrometry in negative ion mode enabled discrimination based on the presence or absence of nine compounds, which were identified by comparison of their MS/MS spectra with those of available standards. Lubricants were successfully detected by LESA from stained fabric surfaces; even following extended periods of time between deposition and sampling. Conclusions: A library encompassing the common components of water‐based lubricants has been established using HRMS and MS/MS to enable identification of personal lubricant formulations and differentiation between suppliers.